PENGARUH MOTIVASI TERHADAP KINERJA PEGAWAI (Studi Pada Kantor Kecamatan Ratahan Kabupaten Minahasa Tenggara) - Kapahang, Febriyani Finda; Rorong, Arie Junus; Tampi, Gustaf Budi (JURNAL ADMINISTRASI PUBLIK, 2015)
Southeast Minahasa Regency is the Effect of Motivation on Employee Performance is still not contributed optimally. Factors that affect employee motivation, among others, job satisfaction and the amount recived by an employee kompensasi. To do a job, the employee should have a high performance. Therefore, it is necessary to effect a good motivation in order to improve the performance of the employees. Motivation is the driving goal, the real goal being the main driving force for a person to attempt to obtain or achieve what he wanted either positive or negative. Performance is the result of the quality and quantity of work achieved by a person in performing its functions in accordance with the responsibilities given to the employees. The purpose of this study was to determine the motivation is there any influence on the performance of employees at the District Office Ratahan Southeast Minahasa Regency. In this study, the method used is quantitative analysis method. While data analysis technique used is the technique of correlation between variables to prove the effect of motivation on employee performance. Based on the results of research conducted and followed by analyzing the data obtained, then the result is that there is a strong relationship between the effect of motivation on employee performance for 0.665%, this means working hypothesis acceptable alternative. The result were obtained coefficient determinant of the remaining 44.22%, 55.78% more influenced by other factors not included in this study. Keywords: Effect Of Motivation